Tumor immune microenvironment changes are associated with response to neoadjuvant chemotherapy and long-term survival benefits in advanced epithelial ovarian cancer: A pilot study - Cao, Guangming; Hua, Dingchao; Li, Jinfeng; Zhang, Xuefang; Zhang, Zhiqiang; Zhang, Bei; Bei, Ting; Cui, Lina; Chen, Shiqing; Wang, Shuzhen; Zhu, Lei (Frontiers in Immunology, 2023)
Little is known about the association between efficacy of neoadjuvant chemotherapy (NACT)/survival and the dynamic change of tumor immune environment (TIME) during treatment in epithelial ovarian cancer (EOC). This study investigated the TIME landscape of treatment-naive EOC tumors using multiplex immunofluorescence and associated the TIME before and after platinum-based NACT with treatment efficacy and prognosis in 33 patients with advanced EOC. NACT significantly increased the density of CD8+ T cells (P = 0.033), CD20+ B cells (P = 0.023), CD56 NK cells (P = 0.041), PD-1+ cells (P = 0.042), and PD-L1+CD68+ macrophages (P = 0.005) in the tissue specimens. Response to NACT was evaluated using CA125 response and chemotherapy response score (CRS). Compared with the non-responders, the responders displayed a larger proportion of tumors showing increase in the infiltration of CD20+ cells (P = 0.046) and in the M1/M2 ratio (P = 0.038) as well as fewer tumors showing increase in the infiltration of CD56bright cells (P = 0.041). No association was found between pre-NACT TIME and response to NACT. Density of pre-NACT CD8+ cells was positively associated with longer progression-free survival (PFS) (P = 0.011) and overall survival (OS) (P = 0.048). Post-NACT CD20+ and CD163+ macrophages (M2) infiltrates were associated with prolonged (P = 0.005) and shortened PFS (P = 0.021), respectively. Increase in the density of CD4+ T cells was predictive for longer PFS (P = 0.022) and OS (P = 0.023). In the multivariate analysis, high density of CD8+ cells pre-NACT (P = 0.042) were independently associated with improved OS.